Right to complain: should Norway be following an appeal scheme more in line with its Scandinavian neighbors for written exams in higher education? - Jon Tømmerås Selvik; Eirik Bjorheim Abrahamsen; Pattamawan Jimarkon; Timothy James Marshall (Discover Education)
Abstract In the Scandinavian countries, students have a right to have their written exam results reviewed or appealed if they are not satisfied and wish to challenge the grading quality. This process is a way to ensure quality in the decision-making. However, there are significant differences between the Scandinavian countries. In Norway, in contrast to Denmark and Sweden, the student is not invited to submit any justification for the appeal, which could influence quality in the process and the output. This also challenges efficient use of resources. In the article, we discuss the quality of the Norwegian regrading scheme, with a focus on elements characterizing good decisions. One aspect is the ability to make the case as well-informed as possible. In the current ‘blind’ regrading scheme, examinators carry out appeal assessments without access to information about the original grade and argumentation from the original examinators and the students filing a complaint, which we argue is key information not to be ignored. Despite arguments in support of the current scheme, such as neutrality, it challenges quality by contributing to increased use of resources, differential treatment, and less informed decisions. Overall, we consider the scheme less appropriate and argue, from a decision-making basis, that there is a need to make changes for a more informed, resource-efficient, and fair scheme. We conclude that Norway should have an appeal scheme more in line with its Scandinavian neighbors.